An unusual case of proctosigmoiditis secondary to arteriovenous fistulization - Strjina, Veljko; Kelley, Scott R. (Turkish Journal of Gastroenterology, 2017)
Abstract Refractory chronic colitis presents a medical and surgical challenge, and underlying etiologies are diverse with potential for misclassification as inflammatory bowel disease. We present an unusual case of chronic proctosigmoiditis with rare vascular etiology. A 48-year-old Caucasian male presented with severe diarrhea, weight loss, and abdominal pain. Computed tomography (CT) suggested proctosigmoiditis. Colonoscopy and biopsy findings were non-specific but were suggestive of ischemic etiology and venous congestion. He was initially treated with antibiotics, steroids, and mesalamine, which did not show any improvement. Mesenteric angiography showed a fairly large irregular and bizarre vessel consistent with a large arteriovenous fistula (AVF) associated with one of the branches of the inferior mesenteric artery. AVF was too large to be embolized, and he underwent a laparoscopic low anterior resection with creation of a coloproctostomy and protective diverting loop ileostomy. An AVF was found at the origin of the ascending left colic artery. Inferior mesenteric vein thrombosis and arteriovenous fistulization are rare vascular causes of chronic proctosigmoiditis, but these should be considered in refractory cases. Both initial diagnosis and surgical treatment can be challenging. Cite this article as: Strjina V, Kelley SR. An unusual case of proctosigmoiditis secondary to arteriovenous fistulization. Turk J Gastroenterol 2017; 28: 408-11.